Validation of an Interactive Simulation Module to Train the Use of a Laparoscopic Insufflator. (February 2014) - van Hove, P. Diederick; Verdaasdonk, Emiel G. G.; Dankelman, Jenny; Stassen, Laurents P. S.
Background . The purpose of this study was to determine construct and face validities of an interactive Web-based module for pneumoperitoneum and insufflator. Methods . Participants were recruited from surgical departments in 2 academic hospitals and 1 large nonacademic teaching hospital. They were stratified into 3 groups based on their laparoscopic experience (A, no experience; B, experience as assistant; and C, experience as primary surgeon). Within each group the participants were randomized into a training subgroup and a control subgroup. All participants performed a theoretical and a practical test. The training participants first completed the module before they performed the tests. The control participants immediately performed the tests. Results were compared between the training and control participants. All training participants filled out a questionnaire on their opinion about the module. Results . In total, 40 participants were enrolled in the study: group A consisted of 20 participants and groups B and C both consisted of 10 participants. The trained participants answered significantly more theoretical questions correctly (8.3 vs 6.6; P < .001), correctly identified more alarm causes (91% vs 86%; P = .014) and made significantly less errors in the practical test (1.5 vs 3.6; P = .001). All 20 trained participants rated the module fairly good and indicated the module to be of additive value to surgical training programs. Conclusions . Training with the interactive web-based module on installation of a pneumoperitoneum and use of an insufflator has a positive effect on both theoretical and practical competence. Construct and face validities were established for this module.